Densidad y estructura de una población del Jaguar (Panthera onca) en la Reserva de la Biosfera Calakmul, Campeche, México) - Aranda, Marcelo (Instituto de Ecología, A.C., 1998)
Jaguar density and population structure were estimated in the Calakmul Biosphere Reserve, through the collection and analysis of their tracks. Fieid work was conducted in a 380 km² area in the Southern part of the reserve, where 18 individuáis were estimated present: 6 adult males, 8 adult females, and 4 juveniles. Population density was one jaguar per 24 to 27 km². Also jaguar home range was estimated in 63 to 79 km² for adult mates and 20 to 26 km² for females.